Application of Student-Centered Learning Model in Guidance and Counseling Course for Students: Penerapan Model Student-Centered Learning pada Mata Kuliah Bimbingan dan Konseling Bagi Mahasiswa - Purnika Sari, Nia Juwita; Dwi Ratnasari; Sri Purnami (Edulab : Majalah Ilmiah Laboratorium Pendidikan, 2024)
Among the student-centered approaches, there is one that stands out: student-centered learning (SCL). This model emphasizes students' ability to learn and make decisions. This research uses a qualitative approach with a case study method; examining how the student-centered learning paradigm is applied in the field of guidance and counseling is the main objective of this research. The informants in this study were field study students in the Islamic Education Program at UIN Sunan Kalijaga Yogyakarta during the period October–November 2023. The students involved were all registered in the guidance and counseling course. Data collection techniques include observation and interviews. Based on the results of the study, it was concluded that the application of the student-centered learning model in guidance and counseling classes B and C in the odd semester of 2023 proved effective in increasing student activeness. The increase in student activity can be seen in the increase in critical thinking skills, communication skills, and skills in solving problems. In addition, the lecturer acts as a facilitator of learning practices and is responsible for overseeing the entire learning process.   Abstrak Diantara pendekatan yang berpusat pada siswa, ada satu yang menonjol: Pembelajaran Berpusat pada Siswa (SCL). Model ini menekankan pada kemampuan siswa dalam pembelajaran dan pengambilan keputusan terkait pertumbuhan. Penelitian ini menggunakan pendekatan kualitatif dengan metode studi kasus, mengkaji bagaimana paradigma pembelajaran yang berpusat pada siswa diterapkan dalam bidang bimbingan dan konseling menjadi tujuan utama penelitian ini. Informan dalam penelitian ini merupakan mahasiswa studi lapangan di Program Pendidikan Agama Islam UIN Sunan Kalijaga Yogyakarta selama periode Oktober–NNovember 2023. Mahasiswa yang terlibat semuanya terdaftar pada mata kuliah Bimbingan dan Konseling. Teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Berdasarkan hasil penelitian, diperoleh kesimpulan bahwa penerapan model Student-Centered Learning pada kelas Bimbingan dan Konseling B dan C pada semester ganjil tahun 2023 terbukti efektif dalam meningkatkan keaktifan mahasiswa. Peningkatan aktivitas mahasiswa dapat dilihat dari meningkatnya keterampilan berpikir kritis, keterampilan berkomunikasi, dan keterampilan dalam memecahkan masalah. Disamping itu, dosen berperan sebagai fasilitator praktik pembelajaran yang bertanggung jawab mengawasi seluruh rangkaian pembelajaran.